Composição e digestibilidade in vitro de genótipos de capim-elefante, aos 56 dias de rebrota - Lima, E. S.; Silva, J. F C; Vásquez, H. M.; Araújo, S. A C; Lista, F. N.; Carneiro, R. F V; Rocha, T. C.; Ruivo, S. C.; Deminicis, B. B.; Costa, D. P B [UNESP] (My University, 2008)
Twelve elephant grass genotypes were evaluated in a randomized blocks design with three repetitions. The experimental parcel was of 4 lines with 3m of length, spaced of 1 m and fertilized with 100 kg of P2O5, 100 kg of N, 60 kg of K2O and 25 kg of micronutrients/ha. Significant differences were observed among the genotypes for neutral detergent fiber (FND), acid detergent fiber (FAD) and lignin. The genotypes CNPGL 92-70-02, CNPGL 91-25-01 and CNPGL 93-32-02 showed low values for FND, FAD and lignin, simultaneously, outstanding between the others. There were no significant differences in the levels of dry matter and crude protein contents and in in vitro dry matter digestibility between the genotypes.
Chemical composition and in vitro dry matter digestibility of elephant grass genotypes, at 56 days re-growth
Keywords: Cultivars; Intraspecific hybrids; Pennisetum purpureum